TRANSFORMASI KAMPANYE POLITIK MELALUI DIALOG PUBLIK (STUDI KASUS PROGRAM “DESAK ANIES” PADA PILPRES 2024) - Prasetyo Bonifasius Sitanggang; Rendra Zakaria (Fakultas Ilmu Komunikasi Universitas Teknologi Sumbawa, 2026)
This study explores how political campaigning transforms through public dialogue by examining the “Desak Anies” program in Indonesia’s 2024 presidential race, tracing the shift from one-way messaging to interactive, deliberative engagement. A qualitative descriptive approach within a constructivist paradigm was employed. Data were gathered via non-participant observation of recorded forums, in-depth interviews, and documentation; analysis followed an interactive cycle (data reduction, display, conclusion/verification), with credibility ensured through source, method, and time triangulation. The fieldwork covered Q&A forums in Jakarta, Bandung, Yogyakarta, and Surabaya between 28 November 2023 and 10 February 2024. Findings reveal a consistent persuasion architecture: communicator credibility (ethos) is demonstrated in situ; messages (logos) are tailored to citizens’ issues; emotional resonance (pathos) complements reasoning; face-to-face channels are amplified by digital circulation; audiences span generations; and effects emerge cognitively, affectively, and in participation, both on-site and online. Conceptually, dialogic campaigning raises the bar of electoral democracy citizens shift from targets of persuasion to co-reasoners; when ethos–pathos–logos are integrated with the SMCR-E framework, competition moves beyond slogans toward public tests of reasoning. The model is replicable across political actors. Keywords: Political Campaigning, Public Dialogue, Political Persuasion, Desak Anies, Deliberative Democracy